Does Informal Learning at Work Differ between Temporary and Permanent Workers? Evidence from 20 OECD Countries - Maria Ferreira Sequeda; Andries de Grip; Rolf Van der Velden (Institute for the Study of Labor (IZA), 2015)
Several studies have shown that employees with temporary contracts have lower training participation than those with permanent contracts. There is, however, no empirical literature on the difference in informal learning on the job between permanent and temporary workers. In this paper, we analyse this difference across 20 OECD countries using unique data from the recent PIAAC survey. Using a control function model with endogenous switching, we find that workers in temporary jobs engage in informal learning more intensively than their counterparts in permanent employment, although the former are, indeed, less likely to participate in formal training activities. In addition, we find evidence for complementarity between training and informal learning for both temporary and permanent employees. Our findings suggest that temporary employment need not be dead-end jobs. Instead, temporary jobs of high learning content could be a stepping stone towards permanent employment. However, our results also suggest that labour market segmentation in OECD countries occurs within temporary employment due to the distinction between jobs with low and high learning opportunities.
Keywords: E24; J24; J41; 330; temporary contracts; informal learning; training; human capital investments